Impact of Time to Castration Resistance on Cytoreductive Radiotherapy in Metastatic Castration-Resistant Prostate Cancer - Mai, Lixin; Zhang, Zitong; Li, Yonghong; Liu, Ruiqi; Li, Jibin; Huang, Sijuan; Lin, Maosheng; Liu, Boji; Cao, Wufei; Wu, Jianhua; Liu, Mengzhong; Zhou, Fangjian; et al. (Frontiers in Oncology, 2020)
Background The role of local radiotherapy in metastatic castration-resistant prostate cancer (mCRPC) remains undefined. This study aimed to identify the value of local radiotherapy and potential candidates for mCRPC. Methods A total of 215 patients with mCRPC treated with or without cytoreductive radiotherapy (CRT) between June 2011 and February 2019 were analyzed. Overall survival (OS) was calculated from the onset of mCRPC. The receiver-operating characteristic (ROC) curve was used to find the cutoff point for time to castration resistance (TCR). Results One-hundred and fifty-five (72.1%) patients received abiraterone after mCRPC, and 54 (25.1%) patients received CRT. The median TCR was 14.9 months. After a median follow-up of 31.7 months, the median OS was 33.3 months. The Eastern Cooperative Oncology Group (ECOG) performance scores 0–1, oligometastases, abiraterone after mCRPC, CRT, and TCR ≥9 months were independent prognostic factors for better OS. Stratified analyses showed improved survival when CRT was applied to patients treated with abiraterone (HR 0.44; 95% CI 0.23–0.83; P = 0.012) and TCR ≥9 months (HR 0.39; 95% CI 0.21–0.74; P = 0.004). The percentage of PSA response after radiotherapy was higher in patients with TCR ≥9 months compared to those with TCR <9 months. No grade 3 or worse adverse events after radiotherapy were reported. Conclusions ECOG performance score, oligometastases, abiraterone application, TCR and CRT were independent prognostic factors for OS in patients with mCRPC. Patients with a short duration of response to primary androgen deprivation therapy were less likely to benefit from CRT.